Capture and identification of coke precursors to elucidate the deactivation route of the methanol-to-olefin process over H-SAPO-34. Issue 58 (16th June 2020) - Yu, Bowen; Zhang, Wenna; Wei, Yingxu; Wu, Xinqiang; Sun, Tantan; Fan, Benhan; Xu, Shutao; Liu, Zhongmin
Abstract : The evolution of retained species during the whole methanol-to-olefins process was revealed with the aid of GC-MS, thermogravimetric analysis (TG) and density functional theory (DFT) calculations. Abstract : The evolution of retained species during the whole methanol-to-olefins process was revealed with the aid of GC-MS, thermogravimetric analysis (TG) and density functional theory (DFT) calculations. Precise routes for the transformation of retained methylbenzenes to methylnaphthalenes were proposed, based on the direct capture of three possible organic intermediates, to explain the catalyst deactivation procedure.